Social Media’s Midlife Crisis? How Public Discourse Imagines Platform Futures - Chelsea Butkowski; Frances Corry (Social Media + Society)
As long-standing social media platforms reinvent themselves and new platforms emerge, recent discourses about social media describe the platform landscape as marked by rising uncertainty and volatility. This article deconstructs popular media narratives of emerging, centralized social media platforms, including TikTok, BeReal, and Threads. Through a qualitative textual analysis of mainstream press discourses, we address the current existential juncture in the social media landscape by examining normative ideals of social media usage and the visions animated by these framings. Our study finds that social media’s imagined futures are refracted through the past, surfacing the fundamental importance of nostalgia in narratives of each platform’s emergence. We describe a persistent entanglement between the ongoing production of speculative discourses about future technologies and a yearning for affective experiences of bygone platforms through the concept of nostalgic anticipation. Nostalgic anticipation provides a framework for understanding how today’s narratives of technological change create idealized visions of a digital past while eliding critiques of the social media industry.